2015
DOI: 10.1039/c5cp05554g
|View full text |Cite
|
Sign up to set email alerts
|

Origins of contrasting copper coordination geometries in crystalline copper sulfate pentahydrate

Abstract: ), with the solution versus gas-phase configurations under debate. The differences are often attributed to the intermolecular interactions between the bulk solvent and the aquated complex, resulting in structures stabilized by extended hydrogen-bonding networks. Yet solution phase systems are difficult to study due to the lack of atomic-level positional details. Crystalline solids are ideal models for comparative study, as they contain fixed structures that can be fully characterized using diffraction techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 60 publications
0
44
0
Order By: Relevance
“…Single point energy calculations were performed on a larger Monkhorst-Pack net of 24 Â 24 Â 24 to compute the densities of states and crystal orbital Hamiltonian populations (COHP). 52 Band structure calculations were performed on a Monkhorst-Pack net of 16 Â 16 Â 16, as no significant improvement was observed on increasing the grid size. Band structures and densities of states (DOS) have been used in combination with crystalline orbitals (CO) and COHP plots to analyse the electronic composition of the bands present in the crystal structures at different pressures.…”
Section: Computational Methodologymentioning
confidence: 99%
“…Single point energy calculations were performed on a larger Monkhorst-Pack net of 24 Â 24 Â 24 to compute the densities of states and crystal orbital Hamiltonian populations (COHP). 52 Band structure calculations were performed on a Monkhorst-Pack net of 16 Â 16 Â 16, as no significant improvement was observed on increasing the grid size. Band structures and densities of states (DOS) have been used in combination with crystalline orbitals (CO) and COHP plots to analyse the electronic composition of the bands present in the crystal structures at different pressures.…”
Section: Computational Methodologymentioning
confidence: 99%
“…The Peintinger-Oliveira-Bredow split-valence triple-ζ (pob-TZVP) basis sets (Peintinger et al 2013) were used for all atoms along with the hybrid Becke-3-Lee-Yang-Parr (B3LYP) functional, which provides excellent results for copper oxysalt crystals (Ruiz et al 2006;Ruggiero et al 2015;Krivovichev et al 2016a, b). Geometry optimization was initiated with experimental determined crystal-structure models determined for clinoclase and gilmarite by Eby and Hawthorne (1990) and Sarp and Černý (1999), respectively (Tab.…”
Section: Density Functional Theory (Dft) Modelingmentioning
confidence: 99%
“…4a). Since gas-phase Cu-H 2 O configurations are always planar (Bryantsev et al 2008), their bending in solid state is usually attributed to the external forces such as a crystalline packing strain and the formation of hydrogen bonds to adjacent anions (Ruggiero et al 2015), which is observed in the crystal structure of euchroite.…”
Section: Resultsmentioning
confidence: 99%
“…The Peintinger − Oliveira − Bredow split-valence triple-ζ (pob-TZVP) basis sets (Peintinger et al 2013) were used for all atoms along with the hybrid Becke-3 − Lee − Yang − Parr (B3LYP) functional, which provides excellent results for copper oxysalt crystals (Ruiz et al 2006;Ruggiero et al 2015). Geometry optimization was initiated with experimentally determined atomic coordinates and the H atoms were allowed to relax.…”
Section: Methodsmentioning
confidence: 99%